Design Study of Thorium Cycle Based Long Life Modular Boiling Water Reactors - Nuri Trianti; Zaki Su’ud; Eka Sapta Riyana (Indonesian Journal of Physics, 2011)
Design study of long life (cycle) Boiling Water Reactor, which can be operated for 20-30 years of operation time without the necessity of refuelling during that period, has been performed. In shown in the previous study Th232-U233 cycle based fuel has potential for longer operation time in the thermal reactor domain. To increase reactor operation time and minimize excess-reactivity burnable poison may be used. Protactinium (Pa-231), Np-238, or gadolinium has good properties for such purpose. Here based on the previous study we select Protactinium and Gadolinium poisons to be used in the present study. Optimizations the content of 231Pa in the core enables the BWR core to sustain enough reactivity for long period of time with reasonable burn-up reactivity swing. Based on the optimization of fuel element composition (Th and Pa) in various moderation compositions can be achieved reactor core with longer operation time, 20 ~ 30 years operation without fuel shuffling or refuelling. Similarly Gadolinium has been successfully used to extend refuelling time and reduce excess reactivity during burnup period for both oxide fuel and nitride fuel.